Measurements of stress fields near a grain boundary: Exploring blocked arrays of dislocations in 3D. (1st September 2015) - Guo, Y.; Collins, D.M.; Tarleton, E.; Hofmann, F.; Tischler, J.; Liu, W.; Xu, R.; Wilkinson, A.J.; Britton, T.B.
Abstract: The interaction between dislocation pile-ups and grain boundaries gives rise to heterogeneous stress distributions when a structural metal is subjected to mechanical loading. Such stress heterogeneity leads to preferential sites for damage nucleation and therefore is intrinsically linked to the strength and ductility of polycrystalline metals. To date the majority of conclusions have been drawn from 2D experimental investigations at the sample surface, allowing only incomplete observations. Our purpose here is to significantly advance the understanding of such problems by providing quantitative measurements of the effects of dislocation pile up and grain boundary interactions in 3D. This is accomplished through the application of differential aperture X-ray Laue micro-diffraction (DAXM) and high angular resolution electron backscatter diffraction (HR-EBSD) techniques. Our analysis demonstrates a similar strain characterization capability between DAXM and HR-EBSD and the variation of stress intensity in 3D reveals that different parts of the same grain boundary may have different strengths in resisting slip transfer, likely due to the local grain boundary curvature.